DESIGN OF A SYSTEM FOR AUTOMATIC MONITORING OF MOBILE TERRITORIALLY SEPARATED OBJECTS - I.A. Kubasov; L.A. Lekar (Надежность и качество сложных систем)
Background. Today, unmanned aerial vehicles (UAVs) are flying devices that can be controlled without human intervention, and are not just a fun toy. They are used to study the earth's surface, monitor forest fires and floods, and much more, and not only for peaceful purposes. At the same time, their capabilities are improving every day, and the scope of application is increasing at an incredible rate. Of particular relevance is the implementation of automatic monitoring of many different moving objects over a multi-kilometer territory to identify possible violations and ensure prompt suppression of these violations. The purpose of this work is to develop proposals for the design of a complex system and the creation of technology for the implementation of automatic monitoring of moving geographically dispersed objects. Materials and methods. The designed complex automatic monitoring system should consist of: a control point with a personal computer and Internet access; one or several UAV placement bases; UAVs with wireless Internet access; applications on smartphones/tablets of the employees of operational response groups to violations. The technology should be comprehensive (hybrid), allowing to obtain the required effect due to the use of UAVs, GLONASS positioning system, Internet of things, computer vision and communication system. Machine learning technologies are supposed to be used to solve the problems of object recognition. Results. Designing an automatic monitoring system for mobile geographically dispersed objects is a complex process that requires the involvement of specialists of various profiles: engineers, programmers, analysts and operators. A correctly designed and implemented system can significantly increase the effectiveness of control over the territory and ensure a timely response to any violations. Conclusions. The proposed system and hybrid technology for automatic monitoring of mobile geographically dispersed objects allow for a synergistic effect due to the integrated use of the GLONASS location system, UAVs, the Internet of Things, computer vision and communication systems.